1992
DOI: 10.1080/02791072.1992.10471632
|View full text |Cite
|
Sign up to set email alerts
|

Affect Regulation, Nicotine Addiction, and Smoking Cessation

Abstract: Numerous investigators have examined the role of negative affective states and affect regulation in the initiation and development of cigarette smoking behavior, smoking cessation, and relapse prevention. Affect regulation refers to any attempt to alleviate negative mood states by means of pharmacologic-, cognitive-, behavioral- or environmental-change methods. The psychological construct/process of affect regulation is examined in relation to (1) the initiation, development, and maintenance of the cigarette s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
95
0
4

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(104 citation statements)
references
References 46 publications
5
95
0
4
Order By: Relevance
“…Nicotine's selective infl uence on low positive affect may be especially clinically salient considering that anhedonia is an important feature of depression (Berenbaum and Oltmanns 1992), a psychiatric disorder that frequently co-occurs with smoking (Glassman et al 1990). Although negative affect has been posited as a mechanism maintaining smoking in depression-prone smokers (Carmody 1992), defi cient positive affect may be an additional pathway infl uencing comorbidity between nicotine dependence and depression. The present fi ndings suggest a need to broaden existing theory about how nicotine's infl uence on positive mood contributes to the development and maintenance of smoking among smokers with comorbid depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine's selective infl uence on low positive affect may be especially clinically salient considering that anhedonia is an important feature of depression (Berenbaum and Oltmanns 1992), a psychiatric disorder that frequently co-occurs with smoking (Glassman et al 1990). Although negative affect has been posited as a mechanism maintaining smoking in depression-prone smokers (Carmody 1992), defi cient positive affect may be an additional pathway infl uencing comorbidity between nicotine dependence and depression. The present fi ndings suggest a need to broaden existing theory about how nicotine's infl uence on positive mood contributes to the development and maintenance of smoking among smokers with comorbid depression.…”
Section: Discussionmentioning
confidence: 99%
“…T he relationship between biopsychosocial vulnerabilities and nicotine dependence has been conceptualized, for the most part, according to a self-medication model (Breslau et al 1993;Carmody 1992;Hall et al 1993). The self-medication hypothesis that posits that persistent negative affect is relieved by the pharmacological effects of smoking has received particular interest as an explanation for the high prevalence of depression among smokers (Glassman et al 1990).…”
mentioning
confidence: 99%
“…12,46 Empiric evidence suggests that the heightened sensitivity of some depressed individuals to nicotine's positive mood-altering effects may lead to selfmedication, which reinforces regular and heavy smoking. [57][58][59][60][61][62][63] Both survey and experimental studies report that nicotine reduces negative mood in smokers, that negative mood within 3 days of attempting to quit is one of the strongest predictors of relapse, that the benefits of nicotine gum are more apparent in depressed smokers, 9,46,64 and that persistent withdrawal symptoms predict major depression following smoking cessation. 65 Even though all retrospective studies indicate that negative mood is a precipitant of relapse, 12 and thereby might maintain an active smoking habit, recall bias may play an important role in the association.…”
mentioning
confidence: 99%
“…65 Even though all retrospective studies indicate that negative mood is a precipitant of relapse, 12 and thereby might maintain an active smoking habit, recall bias may play an important role in the association. 62 One investigation examined a single cohort for relapse and found that negative mood was related to relapse when subjects were questioned after the relapse occurred but that the relation disappeared when the data were examined prospectively. 66 Proposed mechanisms for a causal pathway in the other direction, from smoking to Age-adjusted with respect to the entire cohort population.…”
mentioning
confidence: 99%
“…Specifically, a strong and persistent desire to use tobacco maintains use patterns (Baker, Morse, & Sherman, 1986;Tiffany, 1990) and contributes to difficulties in quitting (e.g., Tracy, 1994). Researchers question whether nicotine's ability to alter emotions (Baker et al, 1986;Carmody, 1990;Hall, Munoz, Reus, & Sees, 1993) drives the motivation to use tobacco products or whether this increased motivation is more automatic (Tiffany, 1990) and independent from emotion (Robinson & Berridge, 2000). Nevertheless, nicotine administration appears to create an intense motivation to use tobacco products that is difficult to break regardless of the mechanism that promotes the powerful desire to continue tobacco use.…”
Section: Other Prominent Criteria For Nicotine Dependencementioning
confidence: 99%